DETERMINANTS OF IMPLEMENTATION SUCCESS IN INDIA'S SMART CITIES MISSION: A NATIONAL COMPARATIVE ANALYSIS - Jaiswal, Amit (International Journal of Research -GRANTHAALAYAH, 2024)
This study presents a comprehensive analysis of implementation outcomes across all 100 cities under India's Smart Cities Mission (SCM), examining 7,983 projects worth Rs. 181,490 crore as of July 2023. Using regression analysis and comparative methods, we identify key determinants of success in urban infrastructure implementation. Our findings reveal significant variation in completion rates (11.8% to 100%), with South Indian cities achieving 78.8% average completion compared to 53.3% in East and Northeast India. The analysis demonstrates that project scale and regional institutional capacity are primary determinants of implementation success, with an intriguing 'investment-implementation paradox' where 74.8% of projects are completed but only 60.7% of investment is utilized. These findings have important implications for urban policy design and federal program management in India.